Interleukin 7 immunotherapy improves host immunity and survival in a two-hit model of Pseudomonas aeruginosa pneumonia. Issue 2 (14th September 2016) - Shindo, Yuichiro; Fuchs, Anja G; Davis, Christopher G; Eitas, Tim; Unsinger, Jacqueline; Burnham, Carey-Ann D; Green, Jonathan M; Morre, Michel; Bochicchio, Grant V; Hotchkiss, Richard S
Abstract: Patients with protracted sepsis develop impaired immunity, which predisposes them to acquiring secondary infections. One of the most common and lethal secondary infections is Pseudomonas aeruginosa pneumonia. Immunoadjuvant therapy is a promising approach to reverse sepsis-induced immunosuppression and improve morbidity and mortality from secondary infections. Interleukin-7 is an immunoadjuvant that improves survival in clinically relevant animal models of polymicrobial peritonitis and in fungal sepsis. This study investigated the effect of recombinant human interleukin-7 (rhIL-7) on survival in a 2-hit model of sublethal cecal ligation and puncture followed by P. aeruginosa pneumonia. Potential immunologic mechanisms responsible for the rhIL-7 putative beneficial effect were also examined, focusing on IL-17, IL-22, IFN-γ, and TNF-α, cytokines that are critical in the control of sepsis and pulmonary Pseudomonas infections. Results showed that rhIL-7 was highly effective in preventing P. aeruginosa –induced death, i.e., 92% survival in rhIL-7–treated mice versus 56% survival in control mice. rhIL-7 increased absolute numbers of immune effector cells in lung and spleen and ameliorated the sepsis-induced loss of lung innate lymphoid cells (ILCs). rhIL-7 also significantly increased IL-17–, IFN-γ–, and TNF-α–producing lung ILCs and CD8 T cells as well as IFN-γ– and TNF-α–producing splenic T cell subsets and ILCs. Furthermore, rhIL-7 enhanced NF-κB and STAT3 signaling in lungs during sepsis and pneumonia. Given the high mortality associated with secondary P. aeruginosa pneumonia, the ability of rhIL-7 to improve immunity and increase survival in multiple animal models of sepsis, and the remarkable safety profile of rhIL-7, clinical trials with rhIL-7 should be considered.